Affective Learning Strategy and Lecturers’ Exemplary: Do They Affect in Shaping Scholars’ Character? - Mujiyanto Mujiyanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
Factors affecting students' character are very various. In this case, it needs a certain study that reveals several specific factors affecting students' character. The objectives of this study is to analyze the influence of affective learning strategies and Lecturers' Exemplary on shaping students' character. The research uses quantitative methods with multiple regression research. The research population was all students of the Buddhist Religious Education Study Program, Raden Wijaya State Buddhist college with the sample used was 33 students. Data collection techniques were carried out by questionnaires. The results of the analysis show that partially affective learning strategies have a significant positive effect in shaping students’ character with a value of sig (p) 0.05 or t obtained t table (6,485 2,045). There is a significant positive effect among lecturers’ exemplary in shaping students’ character with a value of sig (p) 0.05 or t obtained t table (5.566 2.045). Moreover, affective learning strategies and lecturers' exemplary influence simultaneously in shaping students’ character, it is because of the value of sig 0.00 (p) 0.05. Furthermore, the effect is amount to 94.2% and 5.8% is influenced by other variables that have not been studied. Impliciation of this research is that lecturers should keep their attitude, utterance, and behaviour especially in the class because the students tend to imitate  their lecturers.